Ethical Dimensions of Islamic Finance: Lessons from the CSR Model of Indonesian Islamic Banks - Aminudin Ma'ruf; Khairunnisa Nurul Fikri (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
The Islamic financial system is regarded as a financial system that bases its operations on the valuesof Islam. However, the practice of the Islamic financial industry has been criticized as it deviates fromthe theory. This paper aims to explore and analyze the ethical values of Islamic finance and theirimplementation in Indonesian Islamic commercial banks. The study employs a qualitative researchmethod with the literature study approach and assessment of the annual reports of 14 IndonesianIslamic commercial banks. The literature study explores and analyses Islamic values embedded withinthe Islamic financial system. In contrast, the exploration and assessment of Indonesian Islamiccommercial banks’ annual reports provide the study with the practical implementation of the values.The paper found that Indonesian Islamic commercial banks have contributed to facing the currentsocial and environmental issues through some initiatives in their CSR implementations. All IndonesianIslamic commercial banks have been actively participating in CSR programs. However, a number ofIslamic banks need to enhance their CSR practices to tackle the ongoing environmental issues.Therefore, the paper comes with some limitations and policy recommendations.